THE EMPOWERMENT OF THE RUMAH BELAJAR CSR PT. ANTAM TBK. IN IMPROVING EDUCATION TO THE COMMUNITY - Fernandes Arung; S. Sarmadan (Journal of English Education, 2016)
This devotion aimed to improve the service of CSR PT. Antam Ltd. by empowering Rumah Belajar Masyarakat (Home Learning Communities) in the village Hakatutobu, Kecamatan Pomalaa. The issue was raised based on observations made on the activities of Rumah Belajar Masyarakat contributed by the CSR PT. Antam Ltd. which found lack of activity and learning process seemed less maximal for empowerment as its function as a house of learning for communities. This devotion covered four phases of activities, namely: (1) a common approach that takes the form of a preliminary study, (2) determination of the partners and participants of research, (3) the type, data collection procedures, and (4) scale activities. Outputs generated in this devotion are the services, methods, and products